PERKEMBANGAN KEPARIWISATAAN PANTAI BARON DITINJAU MENGGUNAKAN TEORI MIOSSEC - , NURIZKA FIDALI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research basically have three target, that is [1] knowing and documenting tourism in Baron Beach